![1)\ 3(2x + 5) = 6x + 15\\\\2)\ 7(p + 3q) = 7p + 21q\\\\3)\ 3m(n - 2m) = 3mn - 6m^2\\\\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/11gtiglqlsz5d2fq4fh0phos5bk2aqd9i0.png)
Solution:
Given that,
We have to expand the brackets
Use distributive property,
a(b + c) = ab + bc
Multiply the number in front of parenthesis with each term inside the parenthesis and then add them together
1)
![3(2x + 5) = 3 * 2x + 3 * 5\\\\3(2x + 5) = 6x+15](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7pbdtjv7k3wq2qfdiptw4p7j84m26vg60y.png)
-------------------------------------------------
2)
![7(p + 3q) = 7 * p + 7 * 3q\\\\7(p + 3q) =7p + 21q](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zffnoeukkzx2hzi5pdye522c5ne50vrtck.png)
----------------------------------------------------
3)
![3m(n-2m) = 3m * n - 3m * 2m\\\\3m(n-2m) = 3mn - 6m^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1hycypsadi4mzguskx2gacqsv4md2e5667.png)
Thus the given expressions are expanded using distributive property